2023
DOI: 10.3389/fimmu.2023.1191382
|View full text |Cite
|
Sign up to set email alerts
|

Analysis benefits of a second Allo-HSCT after CAR-T cell therapy in patients with relapsed/refractory B-cell acute lymphoblastic leukemia who relapsed after transplant

Abstract: BackgroundChimeric antigen receptor (CAR) T-cell therapy has demonstrated high initial complete remission (CR) rates in B-cell acute lymphoblastic leukemia (B-ALL) patients, including those who relapsed after transplant. However, the duration of remission requires improvements. Whether bridging to a second allogeneic hematopoietic stem cell transplant (allo-HSCT) after CAR-T therapy can improve long-term survival remains controversial. We retrospectively analyzed long-term follow-up data of B-ALL patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A common and challenging side effect associated with CAR T-cell therapy is ICANS, which occurs in 20–60% of patients [ 46 ], of whom 12–30% showed severe (≥grade 3) symptoms. Similar to RR and CRS, a lower event rate in ICANS revealed a better treatment outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common and challenging side effect associated with CAR T-cell therapy is ICANS, which occurs in 20–60% of patients [ 46 ], of whom 12–30% showed severe (≥grade 3) symptoms. Similar to RR and CRS, a lower event rate in ICANS revealed a better treatment outcome.…”
Section: Resultsmentioning
confidence: 99%
“…A recent investigation conducted by Cao et al. aimed to assess the efficacy of employing a second allo-HSCT following CAR T-cell therapy in patients with r/r B-ALL [ 46 ]. Their findings revealed that integrating CAR-T therapy with a subsequent consolidation allo-HSCT significantly enhanced the observed outcomes, with MRD-CR of 90.5% and RR of 10.5% in individuals with r/r B-ALL and post-transplant relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The paradigmatic case of this potential use would be multiple myeloma or NHL, where many patients undergo CAR-T therapy after relapse following autologous transplantation [62]. In the case of LAL, successful cases have been described with the infusion of allogeneic CAR-T cells from the donor after early relapse following allogeneic HSCT [63][64][65]. On the other hand, the hematopoietic toxicities of autologous CAR-T cell therapies are a major concern, and there are many cases reported that have required the infusion of hematopoietic progenitors as rescue [66,67].…”
Section: Car-t Immunotherapymentioning
confidence: 99%
“…The paradigmatic case of this potential use would be multiple myeloma or NHL, where many patients undergo CAR-T therapy after relapse following autologous transplantation [ 70 ]. In the case of LAL, successful cases have been described with the infusion of allogeneic CAR-T cells from the donor after early relapse following allogeneic HSCT [ 71 , 72 , 73 ]. In addition to this, this mobilized product could be used to treat the hematopoietic toxicities of autologous CAR-T-cell therapies, which are a major concern, and there are many cases reported that have required the infusion of hematopoietic progenitors as rescue [ 74 , 75 ].…”
Section: New Cellular Sources For Car Immunotherapy: G-csf Mobilized ...mentioning
confidence: 99%